Organizational reputation: A descriptive study of concept development and measurement techniques - Al-salhi, Hatim Ali H (ALBAHITH ALALAMI, 2020)
The study aimed to monitor the concept of reputation in the previous literature, its relationship to mental image and identity, and to reveal recent trends in its measurement Techniques. The study relied on a descriptive approach using library survey and comparative analysis, and the study reached following conclusions: Despite the beginning of the first signs of reputation In the fifties of the last century, however, Defining and standardizing the concept with clear and specific dimensions began in the 1990s and the beginning of the third millennium. The concept of reputation refers to the stakeholders’ overall evaluation of organizations, which reflects their perceptions of organizations’ performance and their past, present and future actions, and these perceptions are formed over time. The results also showed the existence of several trends for measuring reputation, including trends that narrowed the concept of reputation, or borrowed indicators to measure it from other concepts, but the trend of social expectations is the broader and broader trend where reputation is seen through stakeholders’ multiple expectations from organizations, such as: Fortune Scale, Reputation Quotient Score, RepTrak® system scale, and Helm Scale. The study recommended that organizations consider reputation as an integral part of strategic management and that they establish a reputation management division affiliated to the Public Relations management, and its tasks include monitoring the organization’s reputation in traditional and new media, and evaluating it among stakeholders through field surveys, and reporting with solutions proposals for senior management